2013
DOI: 10.3791/50978
|View full text |Cite
|
Sign up to set email alerts
|

Marble Burying and Nestlet Shredding as Tests of Repetitive, Compulsive-like Behaviors in Mice

Abstract: Obsessive-compulsive disorder (OCD) and autism spectrum disorders (ASD) are serious and debilitating psychiatric conditions and each constitutes a significant public health concern, particularly in children. Both of these conditions are highlighted by the repeated expression of meaningless behaviors. Individuals with OCD often show checking, frequent hand washing, and counting. Children with ASDs also engage in repetitive tapping, arm or hand flapping, and rocking. These behaviors can vary widely in intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
243
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(257 citation statements)
references
References 21 publications
8
243
4
2
Order By: Relevance
“…The data also show that OT-MCH relationship did not extend to exploratory or anxiety related behaviors as assayed through open-field, light-dark box, and elevated plus maze assays. This data support previous reports demonstrating that marble-burying does not reflect an anxiety response (Thomas et al, 2009; Greene-Schloesser et al, 2011; Angoa-Perez et al, 2013; Aguilar-Valles et al, 2015; Mitra et al, 2016a, 2016b, 2017). As previously reported, we also found that OT infusions increased genital grooming but MCH infusions did not (Amico et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data also show that OT-MCH relationship did not extend to exploratory or anxiety related behaviors as assayed through open-field, light-dark box, and elevated plus maze assays. This data support previous reports demonstrating that marble-burying does not reflect an anxiety response (Thomas et al, 2009; Greene-Schloesser et al, 2011; Angoa-Perez et al, 2013; Aguilar-Valles et al, 2015; Mitra et al, 2016a, 2016b, 2017). As previously reported, we also found that OT infusions increased genital grooming but MCH infusions did not (Amico et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…To test whether OT infusion reduces repetitive behavior in mice, we investigated its effect in marble burying task (Deacon, 2006; Thomas et al, 2009; Greene-Schloesser et al, 2011; Angoa-Perez et al, 2013). We found that i.c.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity of rodents to bury unknown objects, such as marbles, underneath cage bedding has been used previously as a screen for anxiety state and compulsive behaviors [38]. …”
Section: Marble Buryingmentioning
confidence: 99%
“…Indeed, MB is a screening test for potential OCD treatments (Egashira et al, 2008;Gyertyan, 1995;Millan, Girardon, Mullot, Brocco, & Dekeyne, 2002). However, the test lacks illness specificity and has been used to model treatment response in impulsivity (Schneider & Popik, 2007), autism (Angoa-Pérez, Kane, Briggs, Francescutti, & Kuhn, 2013), and dementia (TorresLista et al, 2015).…”
mentioning
confidence: 99%